Short Communication: Calcareous nannofossil assemblages and age determination in Leuwi Kenit, Ciletuh Palabuhanratu Geopark, Indonesia - SANTI DWI PRATIWI; NURDRAJAT NURDRAJAT; FITTRIE MEYLLIANAWATY PRATIWY; SHUN CHIYONOBU (Society for Indonesian Biodiversity, 2024)
Abstract. Pratiwi SD, Nurdrajat, Pratiwy FM, Chiyonobu S. 2024. Short Communication: Calcareous nannofossil assemblages and age determination in Leuwi Kenit, Ciletuh Palabuhanratu Geopark, Indonesia. Biodiversitas 25: 3200-3207. Our meticulous and comprehensive investigation of nannofossil diversity in Leuwi Kenit, Sukabumi District, West Java Province, Indonesia, a part of the Ciletuh Palabuhanratu UGG, where the study of nannofossils is limited, is of significant importance their implications for age determination and clarifying the geological history of the region. The initial documentation of calcareous nannofossils in the Leuwi Kenit traverse of the Cikarang Member within the Jampang Formation resulted in the identification of thirty-three species from 62 samples. The studied section reveals seven nannofossil biozones, arranged from oldest to youngest as follows: LO Sphenolithus ciperoensis; LO Cyclicargolithus abisectus; FO Sp. disbelemnos; FCO Helicosphaera carteri; FO Sp. belemnos; LCO Sp. belemnos; LO Sp. conicus and FCO Sp. heteromorphus. Notably, the abundance of Coccolithus pelagicus, Cyclicargolithus floridanus, Reticulofenestra spp., and Sphenolithus spp. characterized their occurrence throughout the section. The diversity and preservation of nannofossils were found to be good, and based on nannofossil biohorizons, the age of Leuwi Kenit spans from 24.3 million years ago to around 17.7 million years ago at Paleogene (Oligocene age) to Neogen Periode (Early Miocene age). Based on the nannofossils assemblages, results show that the area has many important indicator species, making it essential for future research on ancient ocean conditions and past climate changes within this geopark.